Association of child feeding practices with nutritional status of under-two slum dwelling children: A community-based study from West Bengal, India - Dipta K Mukhopadhyay; Apurba Sinhababu; Asit B Saren; Akhil B Biswas (Wolters Kluwer Medknow Publications, 2013)
A cross-sectional study was conducted among 245 under-two slum-dwelling children in Bankura town, West Bengal, to assess their feeding practices and its association with nutritional status. Child's gender, number of family members, standard of living (SLI), and household food security (HFS) were assessed through interview of mothers/ caregivers. Child feeding practices were measured with Composite Child Feeding Index comprising of age-appropriate, multiple, infant and young child feeding (IYCF) indicators and expressed in standardized IYCF score. Weight and length of the children were measured and the nutritional status was assessed using World Health Organization Growth Standard 2006. Standardized IYCF score was significantly lower in undernourished children than those with normal grades. Per unit increase in standardized IYCF score was likely to reduce the prevalence of underweight, stunting and wasting by 2-3% after adjusting for other variables. Low/ very low HFS, low SLI and female gender were associated with underweight and stunting.